Entre amigos - Oz, Amos; García Lozano, Raquel; Oz, Amos. (Madrid : Siruela, 2013)
'On the kibbutz it's hard to know. We're all supposed to be friends but very few really are.' Amos Oz's compelling new fiction offers revelatory glimpses into the secrets and frustrations of the human heart, played out by a community of misfits united by political disagreement, intense dissatisfaction and lifetimes of words left unspoken. Ariella, unhappy in love, confides in the woman whose husband she stole; Nahum, a devoted father, can't find the words to challenge his daughter's promiscuous lover; the old idealists deplore the apathy of the young, while the young are so used to kibbutz life that they can't work out if they're impassioned or indifferent. Arguments about war, government, travel and children are feverishly taken up and quickly abandoned - and amid this group of people unwilling and unable to say what they mean, Martin attempts to teach Esperanto. At the heart of each drama is a desire to be better, more principled and worthy of the community's respect. With his trademark compassion and sharp-eyed wit, Amos Oz leaves us with the feeling that what matters most between friends is the invisible tie of our shared humanity.
El rey de noruega -- Dos mujeres -- Entre amigos -- Padre -- Un niño pequeño -- Por la noche -- Dir Ajlun -- Esperanto.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Kibbutzim -- Fiction; Short stories; Electronic books